Indonesia : Financial Sector Assessment Program-Basel Core Principles Assessment-Detailed Assessment of Compliance. (IMF Staff Country Reports; Country Report ;, 2012)
This paper is a detailed assessment of Indonesia's financial sector-assessment of compliance with the Basel Core Principles for Effective Banking Supervision (BCP) carried out within the framework of the Financial Sector Assessment Program (FSAP). The Indonesian financial sector comprises banks, multi-finance companies, capital market companies, insurance companies, and pension funds. Bank Indonesia (BI), the central bank, is responsible for regulation and supervision of the banking system. The Executive Board recommends effective information exchange arrangements with other financial sector supervisors, and also to bring about amendments to the BI Act.